Celastrol attenuates renal injury in 5/6 nephrectomized rats via inhibiting epithelial–mesenchymal transition and transforming growth factor-β1/Smad3 pathway. Issue 21 (November 2022) - Tang, Yue-Wen; Yang, Ru-Chun; Wan, Feng; Tang, Xuan-Li; Zhang, Hua-Qin; Lin, Yi
Renal injury is an important factor in the development of chronic kidney diseases that pathologically manifested as renal fibrosis and podocyte damage. In the disease state, renal fibroblasts lead to high expression levels of α-smooth muscle actin (α-SMA), while podocytes undergo epithelial–mesenchymal transition, leading to proteinuria. Celastrol, a bioactive compound in the medicinal plant Tripterygium wilfordii, was found to delay the progression of early diabetic nephropathy and attenuate renal fibrosis in mice with unilateral ureteral obstruction. However, its effect on the renal system in 5/6 nephrectomized (Nx) rats remains unknown. The aim of this study was to explore the protective effects of celastrol and its underlying mechanisms in 5/6 Nx rats. We found that 24 h proteinuria and levels of blood urea nitrogen, serum creatinine, triglycerides, serum P, renal index and cholesterol significantly increased ( P  < 0.05), while that of serum albumin decreased significantly in 5/6 Nx rats. After intervention with celastrol, 24 h proteinuria and levels of blood urea nitrogen, serum creatinine, triglycerides, serum P, renal index, and cholesterol significantly decreased, while that of serum albumin significantly increased. Renal tissue pathological staining and transmission electron microscopy showed that celastrol ameliorated kidney injury and glomerular podocyte foot injury and induced significant anti-inflammatory effects. Quantitative polymerase chain reaction (PCR) and western blotting results revealed that nephrin and NEPH1 expression levels were upregulated, whereas α-SMA and Col4a1 expression levels were downregulated in the celastrol group. Celastrol inhibited the expression of transforming growth factor (TGF)-β1/Smad3 signaling pathway-related molecules such as TGF-β1 and P-Smad3. In summary, celastrol contributes to renal protection by inhibiting the epithelial–mesenchymal transdifferentiation and TGF-β1/Smad3 pathways.